Special Topic on 'Teaching Legal Writing' - Legal Education Review (Legal Education Review)
The notion that there is a positive correlation between teaching and research has been challenged over the last three decades. Some studies have claimed that teaching and research are activities independent from each other. Other studies have found a negative correlation between the two activities. Consequently, the existence of a positive correlation between teaching and research cannot be taken as a given. This article contends that a positive correlation between teaching and research is possible, but it has to be constructed through the deliberate adoption of active strategies. Such a positive correlation is only possible with institutional support. The article examines the literature regarding the nexus between teaching and research and identifies the various arguments for and against the existence of a positive correlation between the two. The article then describes how a positive correlation between teaching and research can be deliberately achieved by clarifying the meanings of teaching, research and the relationship between the two. Lastly, the article proposes some active strategies that can be used to enhance the positive correlation between teaching and research within the discipline of law.